2016
DOI: 10.1080/21645515.2017.1264781
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical study and clinical trial of a novel therapeutic vaccine against multi-drug resistant tuberculosis

Abstract: ABSTRACT[Purpose] Multi-drug resistant (MDR), Mycobacterium tuberculosis (TB) is a big problem in the world. We have developed novel TB therapeutic vaccine (HVJ-E/HSP65 DNA CIL-12 DNA).[Methods and Results] DNA vaccine expressing TB heat shock protein 65 and IL-12 was delivered by the hemagglutinating virus of Japan (HVJ)-envelope. This vaccine provided remarkable protective efficacy and strong therapeutic efficacy against MDR-TB and XDR-TB in murine models. Furthermore, this vaccine provided therapeutic effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Okada et al developed a DNA vaccine expressing tuberculosis antigen HSP65 and cytokine IL-12, which was encapsulated by Japanese hemagglutination virus (HVJ). The study found that the ability to induce IFN-γ and IL-12 is stronger when using 100 μg DNA, which was better than the PDD control group ( 156 ). Mangalakumari Jeyanathan et al developed an adenovirus-based tuberculosis vaccine for respiratory inoculation, which provided a valuable reference of aerosol vaccine strategies.…”
Section: Dna Vaccinesmentioning
confidence: 92%
“…Okada et al developed a DNA vaccine expressing tuberculosis antigen HSP65 and cytokine IL-12, which was encapsulated by Japanese hemagglutination virus (HVJ). The study found that the ability to induce IFN-γ and IL-12 is stronger when using 100 μg DNA, which was better than the PDD control group ( 156 ). Mangalakumari Jeyanathan et al developed an adenovirus-based tuberculosis vaccine for respiratory inoculation, which provided a valuable reference of aerosol vaccine strategies.…”
Section: Dna Vaccinesmentioning
confidence: 92%
“…(2) Subunit vaccine: Of the subunit vaccines prepared from some cell components of the MTB complex, BCG polysaccharide and nucleic acid injection (trade name Siqikang) has obtained a new drug certificate in China 18 ; RUTI (prepared from MTB H37Rv cultured under low oxygen, low pH and low nutrient conditions by crushing, detoxification and then embedding in liposomes), 18 and four recombinant protein vaccines (M72/AS01E, H56/IC31, ID93/GLA‐SE, and AEC/BC02) have entered phase I or II clinical trials 20–22 ; (3) DNA vaccine: Of the DNA vaccines constructed from the genes encoding MTB antigen and eukaryotic expression vectors, only Korean GX‐70 (composed of four MTB antigen plasmids and Flt3 ligand) has obtained the approval for phase I clinical trial (http://ClinicalTrials.gov Identifier: NCT03159975), but this study has been withdrawn because of unconfirmed research expenses. Although no TB DNA vaccine has entered the clinical trial status, many results of animal experiments proved that DNA vaccine could provide remarkable protective efficacy and strong therapeutic effect on mouse TB models 23–25 …”
Section: Introductionmentioning
confidence: 99%
“…Although no TB DNA vaccine has entered the clinical trial status, many results of animal experiments proved that DNA vaccine could provide remarkable protective efficacy and strong therapeutic effect on mouse TB models. 23 , 24 , 25 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first experimental DNA vaccine against TB was developed by Lowrie et al in 1994 by cloning the cross-reactive mycobacterial antigen HSP65 in a plasmid [10]. The recombinant plasmid-based DNA vaccines expressing HSP65 have been shown to provide protection against M. tuberculosis challenge in preventive studies in mice [11], and have also shown therapeutic potential in mouse and monkey models of TB [12,13]. A number of DNA vaccines providing protection against TB in animal models have been developed using other cross-reactive antigens of M. tuberculosis, e.g.…”
Section: Introductionmentioning
confidence: 99%